2022
DOI: 10.1111/imj.15720
|View full text |Cite
|
Sign up to set email alerts
|

The workplace and psychosocial experiences of Australian junior doctors during the COVID‐19 pandemic

Abstract: Background Junior doctors experience high levels of psychological distress and emotional exhaustion. The current Coronavirus disease 2019 (COVID‐19) pandemic has resulted in significant changes to healthcare globally, with quantitative studies demonstrating increased fatigue, depression and burnout in junior doctors. However, there has been limited qualitative research to examine junior doctors' experiences, challenges and beliefs regarding management of future crises. Aims To investigate the workplace and psy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 33 publications
(90 reference statements)
0
12
0
Order By: Relevance
“…Research has shown that heavier workloads and longer working hours caused by the pandemic significantly impacted healthcare workers' mental health (Spiers et al, 2021; Varghese et al, 2021; Zhou et al, 2022). As workloads increase, job satisfaction decreases, which results in many leaving the profession (Buchan et al, 2022; Hunter et al, 2022). This is of great concern considering the predicted future global shortage of healthcare workers (Buonsenso et al, 2021; International Council of Nurses, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that heavier workloads and longer working hours caused by the pandemic significantly impacted healthcare workers' mental health (Spiers et al, 2021; Varghese et al, 2021; Zhou et al, 2022). As workloads increase, job satisfaction decreases, which results in many leaving the profession (Buchan et al, 2022; Hunter et al, 2022). This is of great concern considering the predicted future global shortage of healthcare workers (Buonsenso et al, 2021; International Council of Nurses, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…This is of great concern considering the predicted future global shortage of healthcare workers (Buonsenso et al, 2021; International Council of Nurses, 2021). Researchers are urging healthcare organizations to provide supportive conditions, policies focused on improved work environments, staffing adequacy and fair and reasonable workloads (Buchan et al, 2022; Hunter et al, 2022). Hopefully, these measures will assist with burnout and retention challenges caused by the pandemic (Buchan et al, 2022; Hunter et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…There was significant uncertainty regarding the risk of occupational transmission of SARS‐CoV‐2, limited availability of personal protective equipment, social isolation and restrictions on the provision of health care. Through subsequent waves of infection, frontline health care workers in hospital and aged care settings were particularly impacted, with reported concerns including excessive workload, insufficient rest and fatigue, SARS‐CoV‐2 transmission risk, social isolation, financial loss and pervasive uncertainty 43,44 . Smallwood et al.…”
Section: Discussionmentioning
confidence: 99%
“…Open access issues that both skilled healthcare professionals and young doctors experienced. [7][8][9][10] Due to previous observations and hard work on the frontline, during the second wave of the pandemic, the PC unit of Ravenna (Italy) offered a service of consultations (involving mainly PC specialists but also geriatricians and respiratory specialists) to support young doctors operating within SUCCs. Consultations entailed an online debriefing session for case discussion (weekly) and phone calls in case of need on working days.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…These competencies are frequently neglected in the academic and training curricula,5 6 although medical students and junior doctors consider them essential in caring for dying patients. This added to occupational and moral distress, depression and anxiety, and mental health issues that both skilled healthcare professionals and young doctors experienced 7–10…”
Section: Introductionmentioning
confidence: 99%